Your Genes, Your Health : a Critical Family Guide That Could Save Your Life. - Milunsky, Aubrey (Oxford University Press, USA, 2011)
New advances in genetics have dramatically expanded our ability to avoid, prevent, diagnose, and treat a wide range of disorders. Now, more than ever, families need to know about these new discoveries, especially as there are some 7,000 rare genetic diseases that afflict about 1 in 12 of us. In Your Genes, Your Health, Aubrey Milunsky provides an invaluable and authoritative guide to what you should know about your genes. Illustrated with poignant family histories that underscore the lifesaving importance of knowing one's family medical history and ethnic origin, the book highlights the import.